Assessment of alterations in histone modification function and guidance for death risk prediction in cervical cancer patients - Zhao, Tingting; Liu, Bairong; Zhang, Mengyuan; Li, Shiguo; Zhao, Can; Cheng, Li (Frontiers in Genetics, 2022)
Background Cervical cancer is second most lethal malignancy among women, histone modification plays fundamental role in most biological processes, but the prognostic value of histone modification in cervical cancer has not been evaluated. Methods 594 cervical cancer patients from TCGA-CESC, GSE44001 and GSE52903 cohorts were enrolled in the current study, along with the corresponding clinicopathological features, patients with the follow-up time less than one month were removed. 122 histone modification associated signaling pathways were obtained from MSigDB database, activation scores of these pathways were evaluated by “GSVA” package, differentially expressed genes were identified by “limma” package, and pathway enrichment was conducted by “cluster Profiler 4.0” package. The subsequent least absolute shrinkage and selection operator (LASSO) regression analysis performed by “glmnet” package, prognostic nomogram was established by “regplot” package. For the prediction of potential therapeutic drugs, we used the data from GDSC2016 and visualized via “MOVICS”. Results Nine of 23 histone modification associated prognostic genes were identified to construct the prognostic signature by LASSO analysis, named histone modification associated gene (HMAG) signature. Cervical patients with HMAG-H in TCGA-CESC cohort showed a 2.68-fold change of death risk, with the 95% CI from 1.533 to 4.671 (P<0.001), as well as the increased death risk of HMAG-H in GSE44001 cohort (HR:2.83, 95% CI: 1.370-5.849, P=0.005), and GSE44001 cohort (HR:4.59, 95% CI:1.658-12.697, P=0.003). We observed the preferable AUC values of HMAG signature in TCGA-CESC cohort (1-year:0.719, 3-year:0.741 and 5-year:0.731), GSE44001 cohort (1-year:0.850, 3-year:0.781 and 5-year:0.755). And the C-index of the nomogram showed a prognostic value high to 0.890, while the C-index for age is only 0.562, and for grade is only 0.542. Patients with high HMAG score were more suitable for the treatment of CHIR-99021, embelin, FTI-277, JNK-9L, JQ12, midostaurin, PF-562271, pyrimethamine, thapsigargin, and patients with low HMAG score were more suitable for the treatment of BMS-536924, CP466722, crizotinib, PHA-665752, rapamycin and TAE684. Conclusion We comprehensively evaluated the histone modification status in cervical cancer patients and revealed the histone modification associated prognostic genes to construct the HMAG signature, aim to provide the new insight for the prognosis prediction and clinical precise treatment.